1986
DOI: 10.1002/food.19860300342
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic gelation of proteins

Abstract: This paper deals with certain problems concerning the mechanism of thermotropic gelation of globular proteins, using ovalbumin and soy bean globulin fraction as object of study. Protein denaturation has been shown to be an indispensable condition of thermotropic gelation, while the completeness of denaturation changes controls the degree of conversion in the gelation process. The combination of the experimental data obtained indicates that thermotropic gelation involves primarily non-covalen t interactions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…Clearly, this limits the potential for disulfide bond formation as a necessary component in vicilin networks. A similar lack of disulfide bond involvement in network formation has been observed for other plant proteins including sesame (Lakshmi and Nandi, 1979), oat (Ma et al, 1988), and, in some instances, soybean (Bikbov et al, 1986;van Kleef, 1986). This lack of disulfide bond involvement is not characteristic of all plant protein networks; gels from rapeseed (Gill and Tung, 1978) and soy protein (Furukawa and Ohta, 1982; Utsumi and Kinseila, 1985) have been shown to contain disulfide bonds.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Clearly, this limits the potential for disulfide bond formation as a necessary component in vicilin networks. A similar lack of disulfide bond involvement in network formation has been observed for other plant proteins including sesame (Lakshmi and Nandi, 1979), oat (Ma et al, 1988), and, in some instances, soybean (Bikbov et al, 1986;van Kleef, 1986). This lack of disulfide bond involvement is not characteristic of all plant protein networks; gels from rapeseed (Gill and Tung, 1978) and soy protein (Furukawa and Ohta, 1982; Utsumi and Kinseila, 1985) have been shown to contain disulfide bonds.…”
Section: Discussionsupporting
confidence: 53%
“…Investigations of disulfide bond involvement have used a number of different approaches. The solubility of networks in high levels of denaturants has been used to investigate the relative importance of noncovalent interactions and covalent disulfide bonds (Furukawa et al, 1979; Lakshmi and Nandi, 1979;Bikbov et al, 1986;van Kleef, 1986). There is little agreement, however, in the results of these studies with contradictory data for both soy and ovalbumin gels.…”
Section: Introductionmentioning
confidence: 99%
“…When the temperature reached 81"C, the concentration of monomers and dimers decreased. The initial aggregating temperature was consistent with the results of Johnson and Zabik (1981), Bikbov et al (1986), andVan Kleef (1986). Some OV dimers (Fig.…”
Section: Soluble Protein Distributions At Different Temperaturessupporting
confidence: 90%
“…PROTEINS that form gels after heating are referred to as thermotropic proteins, e.g., egg albumen (EA) and ovalbumin (OV)., On heating, the heat-induced conformation of the protein molecules leads to their aggregation into filaments or densely branched clusters, which interact as 'sticky' reactive molecules rather than as unfolded random coils (Clark, 1991). The intermediate protein aggregates, unstable intermediates between the monomers and the network, begin to partially precipitate from solution through aggregation involving intermolecular linkages such as disulfide cross-links (Margoshes, 1990), hydrogen bonds, and hydrophobic interactions (Bikbov et al, 1986;Kato and Takagi, 1987;Koseki et al, 1989;Kato et al, 1990). As a result of such interactions, the viscoelastic three-dimensional protein network is constructed.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for the poor gel-forming properties may be insufficient heating of the protein dispersions; at this high protein concentration the denaturation temperature of the sunflower isolate/helianthinin is approximately 100 • C. 9,127 Below the denaturation temperature there is almost no protein denaturation, which is a prerequisite for gelation. 192 In order to achieve gelation, the protein should be heated to above its denaturation temperature. However, Sánchez and Burgos 190 reported that no gelation of sunflower proteins occurred even after heating to 110 • C.…”
Section: Gel Formationmentioning
confidence: 99%